Einstein and his famous formula E = mc² - Piattella, Oliver F. (Cadernos de Astronomia, 2022)
One of the most popular equations of physics is the famous rest energy formula, E = mc2, derived by Albert Einstein while developing the special relativity theory. The article where the ideas that give origin to this equation are discussed by Einstein is presented here in a direct translation from German to Brazilian Portuguese.
Keywords: Einstein; special relativity; rest energy